Diversity begets diversity: Low resource heterogeneity reduces the diversity of nut‐nesting ants in rubber plantations. (11th October 2021) - Miao, Bai‐Ge; Peng, Yan‐Qiong; Yang, Da‐Rong; Guénard, Benoit; Liu, Cong
Abstract: One of the most general patterns in ecology is the positive relationship between environmental heterogeneity and local diversity. On the one hand, increased resource heterogeneity provides more resources for diverse consumers in the community. On the other hand, increased structural heterogeneity creates variation in the environment's physical structure, thus allowing the coexistence of diverse species with different environmental requirements. Here, we examined the relative importance of resource and structural heterogeneity in determining the taxonomic, functional, and phylogenetic diversity of nut‐nesting ants in natural rainforest and rubber plantation. The species richness of nut‐nesting ants was 70% higher in rainforest than in rubber plantation. The clustered functional and phylogenetic structure in rubber plantation suggested a strong effect of environmental filtering in shaping ant functional and phylogenetic structure. Nesting heterogeneity (nut diversity) was the major factor explaining variation in taxonomic, functional, and phylogenetic diversity, suggesting that resource heterogeneity plays a major role in shaping the biodiversity patterns of nut‐nesting ants. Overall, these results indicate that decreased resource diversity following the conversion of rainforest to rubber plantation can drive biodiversity loss in nut‐nesting ants, through its effect on reducing both ant species, functional, and phylogenetic diversity. The decline in species richness and functional and phylogenetic diversity in the local ant community might have major effects on ecosystem functioning. Abstract : One of the most general patterns in ecology is the positive relationship between environmental heterogeneity and local diversity.